Different effects of anti-TNF-alpha biologic drugs on the small bowel macroscopic inflammation in patients with ankylosing spondylitis - Chitul A.; Voiosu A.M; Marinescu Mădălina; Caraiola Simona; Nicolau Adriana; Badea Georgeta Camelia; Pârvu Magda Ileana; Ionescu R. A.; Mateescu B. R.; Voiosu M. R.; Băicuş C. R.; Rimbaş M. (Sciendo, 2017)
Background & Aims. Considering the ability of anti-TNF alpha drugs to lower the burden intestinal inflammation in patients with inflammatory bowel disease (IBD), and the similarity between IBD and ankylosing spondylitis (AS) regarding inflammatory intestinal involvement, we aimed to investigate the impact of anti-TNF alpha biologic therapy on subclinical intestinal inflammation in AS patients.